A structural equation model to examine the clinical features of mild‐to‐moderate COVID‐19: A multicenter Italian study. Issue 2 (2nd August 2020) - Barillari, Maria Rosaria; Bastiani, Luca; Lechien, Jerome R.; Mannelli, Giuditta; Molteni, Gabriele; Cantarella, Giovanna; Coppola, Nicola; Costa, Giuseppe; Trecca, Eleonora M. C.; Grillo, Calogero; La Mantia, Ignazio; Chiesa‐Estomba, Carlos M.; et al.
Abstract: The purpose of this study was to evaluate the clinical features of mild‐to‐moderate coronavirus disease 2019 (COVID‐19) in a sample of Italian patients and to investigate the occurrence of smell and taste disorders. Infected individuals with suspected (clinical diagnosis) or laboratory‐confirmed COVID‐19 infection were recruited. Patients completed a survey‐based questionnaire with the aim of assessing their epidemiological and clinical characteristics, general otorhinolaryngological symptoms, and smell and taste disorders. A total of 294 patients with mild‐to‐moderate COVID‐19 completed the survey (147 females). The most prevalent general symptoms included fever, myalgia, cough, and headache. A total of 70.4% and 59.2% of patients reported smell and taste disorders, respectively. A significant association between the two above‐mentioned disorders was found ( rs : 0.412; P < .001). Smell disorders occurred before the other symptoms in 11.6% of patients and was not significantly associated with nasal obstruction or rhinorrhea. Interestingly, our statistical analysis did not show any significant difference, either for general symptoms or otorhinolaryngological features, between the clinical diagnosis group and the laboratory‐confirmed diagnosis (polymerase chain reaction) group. The structural equation model confirmed significant standardized paths ( P < .05) between general symptoms, comorbidities, and general otorhinolaryngological complaints in the absence of a significant correlation between these elements and smell and taste alterations. The prevalence of smell and taste disorders in mild‐to‐moderate Italian COVID‐19 patients is significant both in suspected and laboratory‐confirmed cases and reveals a strong correlation between these clinical signs regardless of the presence of general or otorhinolaryngological symptoms, such as nasal obstruction or rhinorrhea. Highlights: This study evaluates the clinical features of mild‐to‐moderate COVID‐19 in a sample of adult Italian patients. The structural equation model (SEM) built to examine the clinical characteristics of the infection, confirms significant standardised paths between all the evaluated variables and underlines the absence of a significant correlation between smell and taste disorders and all the other variables. Furthermore, the study reveals a strong correlation between smell and taste alterations with a significant prevalence of these symptoms both in suspected (clinical diagnosis) and laboratory‐confirmed (pcr) cases.